The truth about the Devlins [compact disc, unabridged] - Scottoline, Lisa (Penguin Audio, 2024)
TJ Devlin is the charming disappointment in the Devlin family, all of whom are lawyers at their eponymous law firm, except him. He works at the firm as its investigator, after rehab for alcoholism and a stint in prison. One night, TJ's older brother John tells him that he killed his client, an accountant, in self-defense, during a fight that ensued after John had confronted the accountant with evidence of embezzlement. TJ and John hurry to the scene, but they find that the accountant has vanished and so has his car. TJ starts investigating, but the next night, police find the accountant dead of an apparently self-inflicted gunshot wound, in a different car and at a different location. Soon a mysterious sedan starts following TJ and John, and the Devlins realize they are in the crosshairs of a conspiracy. TJ will fight to save his family, but what he learns might break them first.